Academic Dishonesty Among Higher Education Students: The Malaysian Evidence (2014 To 2016) - Mustapha, Ramlan; Hussin, Zaharah; Siraj, Saedah; Darusalam, Ghazali (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2017)
Academic dishonesty has become a global issue and this threatens the academic world from time to time, as listed in findings worldwide. This study aims to provide some insight into the activities of academic dishonesty among higher education students in four selected Malaysian public universities. A survey was conducted on 453 Muslim students in 2014, 365 students in 2015 and 320 students in 2016. The data analyzed using SPSS version 20 to detect validity and reliability of findings. The result shows that 47% of students had committed academic dishonesty at least once in 2014; this was prevalent in 51% of students in 2015 and 49% in 2016. Analysis also indicates that the dominant aspects of academic dishonesty include plagiarizing references while completing assignments and accessing information through digital resources. These outcomes could be used by stakeholders and academic institutions to raise the ethical awareness of plagiarism and academic dishonesty among students pursuing further studies. Nonetheless, further research and academic practices are tentatively proposed.